â€œMEMBACAâ€Â KEPEMIMPINANÂ PEREMPUANÂ DALAMÂ RUUÂ KESETARAANÂ DANÂ KEADILANÂ GENDERÂ DENGANÂ PERSPEKTIFÂ MUHAMMADIYAH - Wahid, Wawan Gunawan Abdul (Musawa Jurnal Studi Gender dan Islam, 2012)
The Draft Law on Gender Equality is present in the community through a variety of responses. Response to the RUU-KKG more colored by a misunderstanding. While poisitif response against based on the fact that the RUU-KKG largely do not conflict with religious teachings in Islam. Among the positive response was given by Muhammadiyah as described in this article. The focus of this article is to study RUU-KKG readings on various laws and Tajdid Muhammadiyah the Legal Affairs Committee. Muhammadiyah insights about women's leadership alignments on gender equality. Alignments were seen in the decision, as well as the fatwa discourse proposes that provides an opportunity for women to show up as a leader in various levels in the public space. In fact, of the time of its emergence, the study of the Legal Affairs Committee of the law of women in politics and became a judge can be regarded as a pioneer in its field.